Ekologia jako wartość - językowe środki wartościujące w wybranych artykułach w czasopiśmie "Victor Junior" = Ecology as a value - linguistic means of expressing values in selected articles in "Victor Junior" journal - Grochala, Beata (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
Ecology is an important element of modern human life, and shaping pro-ecological attitudes should start from an early age. Such an initiative comes from, among others, "Viktor Junior" magazine (addressed to children aged 10-12), which devotes a lot of space to the issues of nature, environmental protection, etc.
Keywords: wartości w wychowaniu; postawa proekologiczna; językowe środki wartościowania; czasopismo młodzieżowe; values in education; pro-ecological attitude; linguistic means of values; magazines for young people